Populismo penal e confisco alargado de bens do pacote Anticrime: reflexão político-constitucional e procedimental com base na perda alargada portuguesa - Lima, Francisca Sandrelle Jorge (2021)
This research aims at the political-constitutional and procedural analysis of the extended confiscation of assets, implemented in the Brazilian legal system through art. 91-A of the Brazilian Penal Code and inaugurated by the Anti-Crime Package - Law No. 13.964/2019. The research investigates whether the creation of this criminal law attended to punitive electoral consumerism (legislative penal populism) or if, in fact, it is a viable instrument to combat organized economic crime. The study is developed from conceptual variables of populism, in order to understand the phenomenon in the field of delimitation, which is, specifically, that of Brazilian politics and legislative inflation and other related phenomena such as lawfare. They also adhere to the various confiscatory modalities and international provisions that recommend extended confiscation. Finally, a parallel is drawn between Law no. 5/2002 – with amendments arising from Law no. 30/2017 - which regulates extended confiscation in Portugal and art. 91- A, of the Brazilian Penal Code, outlining measurements on the gaps found in Brazilian legislation in the face of such comparative analysis and the constitutional impacts of such procedural absences. It is concluded, at the end of the research, that the widespread confiscation of Brazilian assets needs to be considered at the procedural operationalization level, in order to function within the constitutional parameters and not become a mere populist casuistry. It is a theoretical research, with a qualitative approach, analytical-comparative procedural technique of bibliographic nature, located under the observational focus of phenomena that involve the subject. The inquiry approach is technical and subjective, with basic typology, correlational design and hypothetical-deductive method. The theme is not exhausted by all its inherent plexus, but the work opens the analysis of a theme timidly touched in Brazilian doctrine. Thus, it explores and describes phenomena to implement and guide later bibliographies related to the proposal of this dissertation.